Phase II Study of Maintenance Rucaparib in Patients With Platinum-Sensitive Advanced Pancreatic Cancer and a Pathogenic Germline or Somatic Variant in BRCA1, BRCA2, or PALB2. Issue 22 (1st August 2021) - Reiss, Kim A.; Mick, Rosemarie; O'Hara, Mark H.; Teitelbaum, Ursina; Karasic, Thomas B.; Schneider, Charles; Cowden, Stacy; Southwell, Traci; Romeo, Janae; Izgur, Natallia; Hannan, Zain M.; Tondon, Rashmi; et al.
Abstract : PURPOSE: Olaparib, a poly (ADP-ribose) polymerase (PARP) inhibitor (PARPi), is approved as maintenance therapy for patients with advanced pancreatic cancer (PC) and a germline BRCA1 or BRCA2 pathogenic variant (PV). This investigator-initiated, single-arm phase II study assessed the role of the PARPi rucaparib as maintenance therapy in advanced PC with germline or somatic PV in BRCA1, BRCA2, or PALB2 . PATIENTS AND METHODS: Eligible patients had advanced PC; germline (g) or somatic (s) PVs in BRCA1, BRCA2, or PALB2, and received at least 16 weeks of platinum-based chemotherapy without evidence of platinum resistance. Chemotherapy was discontinued and patients received rucaparib 600 mg orally twice a day until progression. The primary end point was the progression-free survival (PFS) rate at 6 months (PFS6). Secondary end points included safety, ORR, disease control rate, duration of response, and overall survival. RESULTS: Of 46 enrolled patients, 42 were evaluable (27 g BRCA2, seven g BRCA1, six g PALB2, and two s BRCA2 ). PFS6 was 59.5% (95% CI, 44.6 to 74.4), median PFS was 13.1 months (95% CI, 4.4 to 21.8), and median overall survival was 23.5 months (95% CI, 20 to 27). The PFS at 12 months was 54.8%. ORR of the 36 patients with measurable disease was 41.7% (3 complete responses; 12 partial responses; 95% CI, 25.5 to 59.2), and disease control rate was 66.7% (95% CI, 49.0 to 81.4). Median duration of response was 17.3 months (95% CI, 8.8 to 25.8). Responses occurred in patients with gBRCA2 (41%, 11 out of 27), gPALB2 (50%, 3 out of 6), and sBRCA2 (50%, 1 out of 2). No new safety signals were noted. CONCLUSION: Maintenance rucaparib is a safe and effective therapy for platinum-sensitive, advanced PC with a PV in BRCA1, BRCA2, or PALB2 . The finding of efficacy in patients with g PALB2 and s BRCA2 PVs expands the population likely to benefit from PARPi beyond g BRCA1 / 2 PV carriers.